Knowledge about the correct use of emergency oral contraceptive among nursing students (Horizontes de Enfermería, 2025)
The emergency oral pill contains progestin, which acts by preventing fertilization if administered within the first 72 hours after intercourse. This research aimed to measure students' knowledge about the correct use of this medication. In this study, the non-experimental cross-sectional quantitative approach was used as the methodology. Data collection was carried out using a validated instrument. The sample consisted of 120 Nursing students from the Universidad Técnica de Ambato, from both the basic and professional areas. Among the obtained results, it stands out that, in the basic area, 51% have a high level of knowledge about the generalities of the morning-after pill. Moreover, with more than 40%, the basic area has a medium level of knowledge about the pharmacological action of the pill. This same area has a medium level of knowledge (more than 41%) about the dosage and mode of use of the drug. Regarding the understanding of the adverse reactions caused by the pill, the professional area of the students shows a low level, at 38%. It is concluded that students at the basic level of the Nursing career have a greater knowledge of the morning-after pill compared to the professional area.
Keywords: Knowledge; Emergency contraceptive; Nursing